Examining the hematological manifestations of systemic lupus erythematosus and their impact on patient outcomes - Nosheen Ali Khan, Momina Khadija Abbasi, Nazia Siddiqui, Salma Ambreen Shahab , Shahida Mushtaq , Rabia Sadaf (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: SLE often presents with cytopaenias, that is anaemia, thrombocytopaenia and leucocytopaenia. These expressions can predispose the  disease and change patient management. Studying these manifestations aid in establishing the connection between them and the further course of the diseases and prognosis.